The use of social media as a communication tool by international development organizations: a case study of the United Nations Children’s Fund (UNICEF) in Egypt - Hamad, Inas Taha Abbas (AUC Knowledge Fountain, 2014)
This study investigates to understand how the United Nations development organizations in Egypt can manage social media as a communication tool to achieve their development objectives. A case study of the United Nations Children’s Fund (UNICEF), Egypt, is introduced. Using the Excellence Theory in Public Relations developed by Grunig (2002), this study examines how social media can contribute to the strategic management of the organization, rather than being a messaging, publicity, and media relations function. Through a content analysis of a number of social media pages of the UN organizations in Egypt, and in-depth interviews with four senior communication officers in four UN organizations operating in Egypt, the research shows that most UN organizations in Egypt still struggle with using social media for development purposes. UNICEF Egypt proved to be an “excellent” model for other development organizations to follow by putting clear strategies, planning their social media platforms in the light of the development objectives of the organization, and maintaining a balanced two-way communication mode with stakeholders and target audience. The strategic management of UNICEF Egypt’s social media platform has contributed to the achievement of the organizational objectives, and enhanced its role as a development organization at both local and international levels.